2020
DOI: 10.1101/2020.03.30.20047662
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Demand for hospitalization services for COVID-19 patients in Brazil

Abstract: 16COVID-19 is now a pandemic and many of the affected countries face severe shortages of 17 hospital resources. In Brazil, the first case was reported on February 26. As the number of cases 18 grows in the country, there is a concern that the health system may become overwhelmed, 19 resulting in shortages of hospital beds, intensive care unit beds, and mechanical ventilators. The 20 timing of shortage is likely to vary geographically depending on the observed onset and pace of 21 transmission observed, on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 28 publications
2
51
0
16
Order By: Relevance
“…There have been numerous previous studies which have aimed to forecast the number of hospital beds required for COVID-19 patients [16][17][18][19][20][21][22]54]. Many of these studies published so far have used point estimates, only originating from one study which often does not reflect the context of interest.…”
Section: Summarising Length Of Staymentioning
confidence: 99%
“…There have been numerous previous studies which have aimed to forecast the number of hospital beds required for COVID-19 patients [16][17][18][19][20][21][22]54]. Many of these studies published so far have used point estimates, only originating from one study which often does not reflect the context of interest.…”
Section: Summarising Length Of Staymentioning
confidence: 99%
“…As of July 15, 2020, 264,561 Iranians have been infected with COVID-19, of whom 13,410 are deceased. Due to the rapidly growing number of con rmed cases of COVID-19, there is a worldwide concern that overwhelmed health systems may face shortages of hospital beds, ICU beds, and ventilators [4], as well as burnout and fatigue [24] of healthcare professionals. Lack of resources in the health sector can lead to discrimination in the optimal distribution of medical services during pandemic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Previous experience with other outbreaks such as MERS and pandemic in uenza has shown that identifying high-risk patients for hospitalization can help healthcare providers and emergency staffs in nding patients who would bene t the most from early, available treatments. In addition, policymakers can use this information to forecast healthcare needs [4].…”
Section: Introductionmentioning
confidence: 99%
“…Its high transmissibility, including through asymptomatic cases, and its tendency to lead to severe complications, hospitalizations and deaths, together with the absence of prior immunity (as it is a virus unknown to the human species), inexistence of vaccine or treatment known to be efficacious and the vulnerability of the Brazilian population (living and health conditions), mean it can assumed that infection incidence will be high and that the number of severe cases, needing hospitalization and/ or intensive care, may exceed health service capacity. 26 In this context it is recommendable to adopt measures that contribute to flattening the COVID-19 epidemic curve, preventing an abrupt increase in the number of cases and reducing the peak in demand for health services. The aim is to avoid the health system from becoming overloaded and collapsing, which could lead to increased mortality owing to lack of hospital beds and intensive care.…”
mentioning
confidence: 99%